2019
DOI: 10.1038/s41419-019-2175-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria ubiquitin ligase, MARCH5 resolves hepatitis B virus X protein aggregates in the liver pathogenesis

Abstract: Infection of hepatitis B virus (HBV) increase the incidence of chronic liver disease and hepatocellular carcinoma (HCC). The hepatitis B viral x (HBx) protein encoded by the HBV genome contributes to the pathogenesis of HCC and thus, negative regulation of HBx is beneficial for the alleviation of the disease pathogenesis. MARCH5 is a mitochondrial E3 ubiquitin ligase and here, we show that high MARCH5 expression levels are correlated with improved survival in HCC patients. MARCH5 interacts with HBx protein mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…MARCH5 is an outer mitochondrial membrane E3 ligase, which is found to interact with HBx to promote the degradation of HBx protein aggregates via the ubiquitin proteasome system. As a result, overexpression of MARCH5 attenuates HBV-induced hepatic inflammation and mitophagy, and MARCH5 expression is positively correlated with the survival of HCC patients [180]. However, whether this declined mitophagy is due to less HBx protein or profound degradation of the mitophagy receptor FUNDC1 remains unknown.…”
Section: Mitophagy In Viral Hepatitismentioning
confidence: 99%
“…MARCH5 is an outer mitochondrial membrane E3 ligase, which is found to interact with HBx to promote the degradation of HBx protein aggregates via the ubiquitin proteasome system. As a result, overexpression of MARCH5 attenuates HBV-induced hepatic inflammation and mitophagy, and MARCH5 expression is positively correlated with the survival of HCC patients [180]. However, whether this declined mitophagy is due to less HBx protein or profound degradation of the mitophagy receptor FUNDC1 remains unknown.…”
Section: Mitophagy In Viral Hepatitismentioning
confidence: 99%
“…MARCH5 along with Mfn1 maintain mitochondrial homeostasis and cell survival [51][52][53][54]. Moreover, MARCH5 decreased the HBx-induced NF-κB and COX-2 activity which may play important roles in carcinogenesis [50,55,56]. The authors further demonstrated that MARCH5 mRNA and protein expression in either HCC or HBV-mediated HCC liver tissue specimens of clinical cases were significantly downregulated in a later stage (Stage IV) of cancers with high expression of HBx [50].…”
Section: Hbxmentioning
confidence: 84%
“…Moreover, MARCH5 decreased the HBx-induced NF-κB and COX-2 activity which may play important roles in carcinogenesis [50,55,56]. The authors further demonstrated that MARCH5 mRNA and protein expression in either HCC or HBV-mediated HCC liver tissue specimens of clinical cases were significantly downregulated in a later stage (Stage IV) of cancers with high expression of HBx [50]. In addition, AIM2 (absent in melanoma2) protein could be involved in cell proliferation and tumorigenic reversion and Aim2 deficient mice are more susceptible to the development of colonic tumor [57,58].…”
Section: Hbxmentioning
confidence: 98%
See 2 more Smart Citations